2018
DOI: 10.1249/mss.0000000000001624
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring at High Altitude—Effects on Glucose Homeostasis

Abstract: We observed a significant increase in nocturnal CGM glucose at 3600 m and greater despite gradual ascent from 1100 m. Taken with the changes in insulin resistance and beta-cell function, it is possible that the stress response to high altitude dominates exercise-enhanced insulin sensitivity, resulting in relative hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…40 Another study performed in an Andean population reported a lower waist circumference at a higher elevation; an adjusted inverse association between geographical elevation and obesity that varied by sex was also found. 21 Furthermore, lower fasting glucose and better glucose tolerance were associated with a high elevation, 33,[41][42][43] and lower prevalence 22,44 and incidence 23,24,45 of overweight or obesity were also found in residents at high elevation.…”
Section: Discussionmentioning
confidence: 95%
“…40 Another study performed in an Andean population reported a lower waist circumference at a higher elevation; an adjusted inverse association between geographical elevation and obesity that varied by sex was also found. 21 Furthermore, lower fasting glucose and better glucose tolerance were associated with a high elevation, 33,[41][42][43] and lower prevalence 22,44 and incidence 23,24,45 of overweight or obesity were also found in residents at high elevation.…”
Section: Discussionmentioning
confidence: 95%
“…61 Although there is conflicting evidence on glycemic control at altitudes between 1500 m (4,920 ft) and 4000 m (13,120 ft), 36 several studies have observed increased insulin requirements above 4000 m (13,120 ft) in those with type 1 diabetes. 35,36 Relative hyperglycemia 62 and insulin resistance at extremely high altitudes in people without diabetes have been reported as well. 36,63,64 It is unclear whether this observed insulin resistance is a result of acute mountain sickness or exposure to hypobaric hypoxia.…”
Section: Change In Insulin Requirementsmentioning
confidence: 86%
“…The observed diabetes management inertia contributing to hyperglycemia among our patients could be potentially explained by the perceived exertion, which increased together with the altitude reached. It was also postulated that the stress response to high altitude dominates exercise-enhanced insulin sensitivity, resulting in relative hyperglycemia [ 19 ]. Of interest, the rise in glucose concentration could not be fully explained by the rise in lactate concentration alone, as the positive correlation was found only for day 2.…”
Section: Discussionmentioning
confidence: 99%